Intensive Care Unit-Acquired Weakness: A Review of Recent Progress With a Look Toward the Future - Wang, Wenkang; Xu, Chuanjie; Ma, Xinglong; Zhang, Xiaoming; Xie, Peng (Frontiers in Medicine, 2020)
Intensive care unit-acquired weakness (ICU-AW), a common neuromuscular complication associated with patients in the ICU, a type of skeletal muscle dysfunction that commonly occurs following sepsis, mobility restriction, hyperglycemia, and the use of glucocorticoids or neuromuscular blocking agents. ICU-AW can lead to delayed withdrawal of mechanical ventilation and extended hospitalization. Patients often have poor prognosis, limited mobility, and severely affected quality of life. Currently, its pathogenesis is uncertain, with unavailability of specific drugs or targeted therapies. ICU-AW has gained attention in recent years. This manuscript reviews the current research status of the epidemiology, pathogenesis, diagnosis, and treatment methods for ICU-AW and speculates the novel perspectives for future research.